Multiple-Temperature Gas-Kinetic Scheme for Type IV Shock/Shock Interaction (Communications in Computational Physics, 2021)
In this paper, a gas-kinetic scheme (GKS) method coupled with a three temperature kinetic model is presented and applied in numerical study of the Edney-type IV shock/shock interaction which could cause serious problems in hypersonicvehicles. The results showed very good agreement with the experimental data inpredicting the heat flux on the surface. It could be obviously seen that the currentmethod can accurately describe the position and features of supersonic jets structureand clearly capture the thermal non-equilibrium in this case. The three temperaturekinetic model includes three different models of temperatures which are translational,rotational and vibrational temperatures. The thermal non-equilibrium model is usedto better simulate the aerodynamic and thermodynamic phenomenon. Current resultswere compared with the experimental data, computational fluid dynamics (CFD) results, and the Direct Simulation Monte Carlo (DSMC) results. Other CFD methodsinclude the original GKS method without considering thermal non-equilibrium, theGKS method with a two temperature kinetic model and the Navier-Stokes equationswith a three temperature kinetic model, which is the same as the multiple temperature kinetic model in current GKS method. Comparisons were made for the surfaceheat flux, pressure loads, Mach number contours and flow field values, including rotational temperature and density. By Comparing with other CFD method, the currentGKS method showed a lot of improvement in predicting the magnitude and positionof heat flux peak on the surface. This demonstrated the good potential of the current GKS method in solving thermodynamic non-equilibrium problems in hypersonicflows. The good performance of predicting the heat flux could bring a lot of benefit forthe designing of the thermal protection system (TPS) for the hypersonic vehicles. Bycomparing with the original GKS method and the two temperature kinetic model, thethree temperature kinetic model showed its importance and accuracy in this case.